Zmiany frakcji hemoglobinowej we wczesnej i późnej samoistnej restytucja po wysiłku wytrzymałościowym mężczyzny w 6 dekadzie życia. Opis przypadku = Change the hemoglobin fraction in the early and late intrinsic restitution after exercise endurance of a man in the 6th Decade of life. Description of the case - Mrozkowiak, Mirosław; Sokołowski, Marek (Journal of Education, Health and Sport, 2016)
Mrozkowiak Mirosław, Sokołowski Marek. Zmiany frakcji hemoglobinowej we wczesnej i późnej samoistnej restytucja po wysiłku wytrzymałościowym mężczyzny w 6 dekadzie życia. Opis przypadku = Change the hemoglobin fraction in the early and late intrinsic restitution after exercise endurance of a man in the 6th Decade of life. Description of the case. Journal of Education, Health and Sport. 2016;6(5):193-210. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.51448 http://ojs.ukw.edu.pl/index.php/johs/article/view/3519 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.04.2016. Revised 25.04.2016. Accepted: 05.05.2016. Zmiany frakcji hemoglobinowej we wczesnej i późnej samoistnej restytucja po wysiłku wytrzymałościowym mężczyzny w 6 dekadzie życia. Opis przypadku Change the hemoglobin fraction in the early and late intrinsic restitution after exercise endurance of a man in the 6th Decade of life. Description of the case 1Mirosław Mrozkowiak, 2Marek Sokołowski 1Bioergonsport, Nowa Biała 8p, 09-411 Biała 2Akademia Wychowania Fizycznego, ul. Królowej Jadwigi 27/39, Poznań Autor: dr Mirosław Mrozkowiak1, dr Marek Sokołowski2 1Bioergonsport, Nowa Biała 8p, 09-411 Biała 2Akademia Wychowania Fizycznego, ul. Królowej Jadwigi 27/39, Poznań Słowa kluczowe: wysiłek wytrzymałościowy, wczesna i późna samoistna restytucja, hemoglobina. Keywords: endurance effort, early and late spontaneous recovery, hemoglobin. Streszczenie Wprowadzenie. Systematycznie realizowana praca wytrzymałościowa umożliwia utrzymanie do późnych lat wysokiego poziomu aktywności enzymów utleniających, przy niezmiennej kapilaryzacji. Jednak po jej wykonaniu jedyną metodą powrotu do stanu zbliżonego sprzed wysiłku jest wypoczynek. To przerwa czasowa pomiędzy jedną a druga pracą, w okresie której wybrane cechy winny przyjąć wielkości odpowiadające fazie superkompensacji, a dalej conajmniej powrócić do stanu wyjściowego. Celem pracy jest wykazanie zmian w wielkości różnych frakcji hemoglobuliny we wczesnej i późnej restytucji samoistnej po wysiłku wytrzymałościowym u mężczyzny w 6 dekadzie życia. Materiał i metody. Badany mężczyzna realizujący zdrowy styl życia poddał się oznaczeniu wybranych wskaźników krwi po wysiłku wytrzymałościowym w czasie restytucji samoistnej: wskaźnik hematokrytowy (HCT), wskaźnik średniego stężenia hemoglobiny w erytrocytach (MCHC), wskaźnik masy hemoglobiny (MCH), stężenie hemoglobiny (HGB), hemoglobina całkowita (tHb), oksyhemoglobina (O2Hb), hemoglobina tlenkowęglowa, karboksyhemoglobina (COHb), deoksyhemoglobina (HHb), methemoglobina (MeHb), Uzyskane wyniki. Pozytywne wyniki zaobserwowano w większości mierzonych cech krwi. Przy czym różnie prezentowała się ich konfiguracja w trakcie 5 dniowego cyklu pomiarowego. Najbardziej dynamiczne zmiany zaobserwowano w wielkości: O2Hb, HCT, COHb, MeHb, HGB, tHb, mniej intensywne w: MCH, MCHC, HCT. Wnioski. (1) Proces wczesnej i późnej restytucji po wysiłku wytrzymałościowym u 61 letniego mężczyzny przebiega zgodnie z ogólnie przyjętymi przedziałami czasowymi. Okres wczesnej odnowy trwa 3-4 godziny, a późnej kończy się po 45 godzinie od zakończonej pracy, (2) Dla określenia dokładniejszych stref czasowych występowania wczesnej i późnej restytucji wymagane byłyby badania na stosunkowo większej populacji po wysiłkach fizycznych angażujących odmienne zdolności motoryczne o różnych parametrach, różnej płci i wieku. Summary Introduction. Systematically performed endurance work enables one to maintain, even in the old age, a high level of oxidizing enzymes and unchanged capillarization. After endurance effort, however, the only way to return to the physical stare from before the exercise is rest. It is during this period that comes between one work and the other that selected blood features should assume values tantamount to supercompensation phase and then return to their initial values. The aim of the present study is to show the changes in the levels of various haemoglobin fractions as observed in a man in his sixties during the early and late spontaneous restitution after endurance effort. Materials and methods. The studied male individual who lives a healthy life-style subjected himself to the markings of selected blood indicators after endurance effort during spontaneous restitution: haematocrit (HTC), mean corpuscular haemoglobin concentration (MCHC), mean corpuscular haemoglobin (MCH), haemoglobin concentration (HGB), total haemoglobin (tHb), oxyhaemoglobin (O2Hb), carbonmonooxide haemoglobin, karboksihaemoglobin (COHb), deoxyhaemoglobin (HHb), methaemoglobin (MeHb). Results. Positive results were observed in most of the measured blood features. However, their configuration in 5-day measurement cycle varied. The most dynamic changes were observed in the following: O2Hb, HCT, COHb, MeHb, HGB, tHb, and less intensive for: MCH, MCHC, HCT. Conclusion. (1) The process of early and late restitution after endurance effort in a 61 year-old male individual runs accordingly to the commonly accepted time intervals. Early restitution period lasts 3-4 hours, and it ends 45 hours after the finished work (2). In order to more accurately determine time frames of the early and late restitution the research on a relatively larger population of varied sex and age is required; such a research would have to be conducted both before and after the physical efforts and it would have to engage various motoric functions of the studied individuals.